Implementation Analysis of Network Core Redundancy Using HSRP and VRRP Protocols for Enterprise Infrastructure Reliability Assurance - Firdaus Syah, Tengku; Adriyanto, Sopan (Yayasan Kawanad, 2025)
This study examines the role of redundancy protocols in enhancing the reliability of core networks within enterprise infrastructures. The research is motivated by the growing reliance of organizations on network-based services and the increasing risks of financial losses caused by downtime, which are projected to escalate alongside global traffic growth. A simulation-based approach was conducted using Cisco Packet Tracer to compare baseline networks without redundancy against implementations of Hot Standby Router Protocol (HSRP) and Virtual Router Redundancy Protocol (VRRP). The evaluation focused on key performance indicators, including failover time, uptime rate, packet loss, latency, and jitter. The results demonstrate that both protocols successfully provided automatic recovery mechanisms, achieving an average failover time of less than five seconds while maintaining stable connectivity. Further analysis revealed that HSRP excels in failover speed, whereas VRRP offers cross-vendor flexibility with consistent stability. These findings confirm that redundancy protocol selection should align with specific network requirements, yet both HSRP and VRRP have proven effective in minimizing downtime risks and ensuring service continuity in enterprise-scale environments.